A artéria celíaca em Didelphis albiventris (gambá) - Culau, Paulete de Oliveira Vargas; Reckziegel, Sueli Hoff; Goltz, Laura Ver; Araújo, Ana Cristina Pacheco de (Acta Scientiae Veterinariae, 2018)
Background : : : : This member of the Didelphidea family, commonly known as opossum, is widely distributed in the American territory, with species found from southern Canada up to northern Argentina. Similarly to all marsupials, they are characterized by a short gestational period, followed by a long development period. Opossums are arboreal, terrestrial slow animals of lonely and nocturnal habits. They are omnivore animals, eating from small rodents, birds, eggs and amphibians to fruits and vegetables. These general characteristics have drawn in the interest and curiosity of the scientific community to this animal, which is now the object of study in several knowledge areas. In order to find morphological information that could assist in discussions from a functional point of view and that could offer support for measures that aim at protecting opossums in their natural environment, the objective of the present study is to divulge the anatomical behavior of their celiac artery and its branches, including its distribution areas, considering the importance of these vessels in the blood supply of several digestive organs. Materials, Methods & Results: In this study, the celiac artery of 24 opossums (Didelphis albiventris), of which 17 were females and 7 were males, was systematized. For the purpose, their arterial system was filled with colored latex 603. The abdominal aorta gave off its first visceral collateral branch, the celiac-mesenteric trunk, which originated the celiac artery and the cranial mesenteric artery in 87.5% of the samples, but in 12.5% of the samples, the abdominal aorta gave off these arteries individually. The celiac artery gave off the lienal and hepatic arteries. The lienal artery gave off the left gastric artery to the lesser curvature of the stomach, supplying its parietal and visceral side, also giving off esophageal branches. The lienal artery reached the splenic hilum, giving off several pancreatic branches during its path. Once it reached the splenic hilum, it gave off its own lienal branches and then continued as left gastroepiploic artery towards the greater stomach curvature. The hepatic artery was projected cranially, giving off the gastroduodenal artery and cranial pancreaticoduodenal artery reaching the portal fissure, where hepatic branches arose towards the liver. The gastroduodenal artery gave off the right gastroepiploic artery towards the greater curvature of the stomach, also giving off the right gastric artery towards the lesser curvature of the stomach and then became divided into one branch to the visceral side and one branch to the parietal side, also giving off esophageal and pyloric branches. The cranial pancreaticoduodenal artery branched to the cranial duodenum and right lobe of the pancreas. Discussion: In the majority of opossums (87.5%), the celiac artery had origin in a common trunk with the cranial mesenteric artery, but in 12.5% of the animals, this origin took place separately. In opossums (Didelphis albiventris), regardless of its origin, the celiac artery was a single vessel and, essentially, it was divided into the hepatic artery and the lienal artery in 100% of the samples. The left gastric artery arose from the lienal artery, next to the origin of this latter in the celiac artery, similarly to the findings in the collared peccary, swine and equine. Therefore, the celiac artery, through its branches, was the artery responsible for the blood supply of the stomach, pancreas, liver, spleen and first part of the duodenum.